CURRY PASTE SUPPLY CHAIN OF COMMUNITY ENTERPRISE IN SURAT THANI PROVINCE - สังข์คร, เตชธรรม (RMUTT Global Business and Economics Review, 2017)
The objective of this research is to study the supply chain process for curry paste community enterprise group in Surat Thani province. This includes production inputs, process, cost and return, and curry’s marketing. Structured interviews were used to collect information from 10 of curry paste production community enterprise group sellers. The researchers collected data manually and analyzed statistics including amount and percentages by using Microsoft Excel and statistical software. The results of the study show community enterprise group mainly manufacture curry and sell for extra income. The period of business operation is between 11-20 years, with approximately 20 members. Average initial business investment is 197,130 Baht. There are three kinds of curry paste manufactured by the community enterprise group. Roasted curry is produced the most, and amounts to 750 kilograms per month. The second is yellow curry of 450 kilograms per month. Thirdly, 300 kilograms per month, is green curry. The raw material used in the production first purchased from the community. If this is not sufficient then wholesale market in the city will be the second choice. Yellow curry has the highest cost in the cost of production. Followed respectively by the green curry and roasted curry. The community enterprise group prices curry paste similarly for all of three types curry paste. Retail price is 120 baht per kilogram, and wholesale price is 100 baht per kilogram. The yellow curry paste wholesale price sells for 1.04 baht less per kilogram. Curry paste community enterprise group found that 90 percent is sold retail. Members of the group sell in the community market includes flea market, municipal market, schools, hotels and exhibition. Wholesalers use middlemen to sell in the flea market to the consumer.